Development of an enzyme-linked immunosorbent assay for the efficient detection of autoantibodies against nuclear valosin-containing protein-like protein (NVL) 2 using its manipulated cDNA - Mariko Ogawa-Momohara; Yoshinao Muro; Masashi Akiyama; Yasuhiro Kondoh; Yasuhiko Yamano; Yuta Yamashita; Haruka Koizumi; Satoshi Kamiya; Norika Akashi; Takuya Takeichi (RMD Open)
Purpose Antinuclear valosin-containing protein-like protein (NVL) antibodies have been detected only in systemic sclerosis (SSc) patients, and diverse comorbidities have been reported in anti-NVL antibody-positive SSc patients. Any relationship between antibodies against NVL1, a minor isoform of NVL, and the clinical symptoms also remains unclear. To clarify the clinical features of anti-NVL2 antibody-positive patients, we developed an ELISA for measuring antibodies against NVL2, a major target of autoantibodies against NVL.Methods Sera from 1676 patients with various conditions were included. 167 anti-nucleolar antibody (ANoA)-positive sera, 120 ANoA-negative sera and 17 healthy control sera were examined by an ELISA that uses the recombinant protein of NVL2 derived from its gene-manipulated complementary DNA clone (modified NVL2 (mNVL2)).Results 18 ANoA-positive sera subjected to indirect immunofluorescence (IIF) were positive for anti-mNVL2 ELISA. Although one ANoA-negative serum was judged false positive in our anti-mNVL2 ELISA, the above 18 anti-mNVL2 ELISA-positive sera were confirmed to be positive for anti-NVL2 antibodies by immunoprecipitation-Western blotting. Anti-NVL2 antibodies were detected in 17.0% of homogeneous nucleolar (AC-8) patterns in IIF. Six SSc patients had anti-NVL2 antibodies, whereas five with idiopathic interstitial pneumonia and seven with other diseases had anti-NVL2 antibodies. Anti-mNVL2 ELISA titres were significantly higher in the anti-NVL2 antibody-positive SSc patients than in the anti-NVL2 antibody-positive non-SSc patients (p<0.042).Conclusions We found more anti-NVL2 antibody-positive cases than any previous study, as far as we know. Our ELISA, which showed an association between titres of these antibodies and SSc diagnosis, promises to expand knowledge about anti-NVL2 antibodies.